Achieving forms of sustainable and competitive tourism in coastal areas: the case of Baixo Vouga - Albuquerque, H
Tourism has become the world’s largest industry, and has overcome economic sectors such as oil production and car manufacturing. It is foreseen that tourism will continue to expand in the future and will spread all around the world. In Europe, the tourism sector is made of 440 million international arrivals that are responsible for accounting about 10% of European GDP and generating 20 million jobs. Coastal destinations are major tourist destinations. This is due to their physical attractiveness, beautiful landscapes, and fine open space for leisure activities. Nevertheless, sun-sea-sand tourism depends very much on the environment. In this way, coastal destination ought to be properly planned so they do not exceed the limits of acceptable change (LAC) of the ecosystems, and keep their attractiveness. Being an economic activity, it is essential that coastal tourism is competitive, and show capacity to attracting new and enlarged markets. Coastal destinations should diversify its products and services, smooth seasonality and become more competitive. Diversification should create more growth and employment, and also reduce environmental, economic and social impact caused by the concentration of tourism activity in a few months of the year and the use of only the beach resource. This paper aims at analyzing the application of the competitiveness concept to tourism in coastal areas (Ria de Aveiro region, Central Portugal), and draws attention to the principle of environmental, economical and social sustainability.